A review on charred traditional Chinese herbs: carbonization to yield a haemostatic effect - Zhi Chen (Taylor & Francis Group, 2019)
Context: Charcoal of Chinese drugs is a kind of special processing product in Chinese medicine and used for treatment of haemoptysis, hematemesis and haemorrhage in the clinic during ancient times. During carbonizing, significant changes occur in chemical constituents and the efficacy of haemostasis will be enhanced. But the quality control standard of ‘carbonizing retains characteristics’ should be followed. Objective: This review introduces the typical methods of carbonizing, which highlight current research progress on haemostatic substances of charcoal drugs so as to provide a reasonable explanation for the theory of haemostasis treated by charcoal medicine. Methods: English and Chinese literature from 2004 to 2019 was collected from databases including Web of Science, PubMed, Elsevier and CNKI (Chinese). Charcoal drug, chemical constituents, processing, haemostasis and carbon dots were used as the key words. Results: Charcoal drugs mainly play a haemostatic role and the effect can be classified into four types to stop bleeding: removing blood stasis, cooling blood, warming meridians and astringing. Changes in composition lead to changes in pharmacodynamics. Carbonizing methods and basic research on haemostasis material in charcoal drugs have also been summarized. Conclusions: This review summarizes the classification of charcoal drugs and highlights the possible material bases for the haemostatic effect of charcoal drugs in recent years, providing new insights to future research.